MODEL PENANGANAN E-MAIL SPAM DENGAN PENDEKATAN TEKNIK SMTPI - Nandang Iriadi (Paradigma, 2009)
The ability to use e-mail as essential to the ability to use the phone. E-mail system is very important thatmany people would complain if the e-mail system can not waste bekerja.E-mail (SPAM) is a problem almostall Internet users and the various efforts to control has been done. Without knowing the factors that causethe occurrence of SPAM, then this problem will still continue. This paper set forth an analysis of SPAM withSMTP Method I, to find fault in the system and the significant factors that cause other Spam.Analisisontology of the system architecture of e-mail describing the parts and systems so that such connectednesscan identify system weaknesses. Then all the significant factors associated with each other by relations ofcausality and proven method SMTPI messages sent by SMTP will be sent in the queue. SMTP will avoidreplying to the message from the queue if connected to a remote machine .. is the use of filtering solutionsthat are considered quite effective from the technical point of view. filtering is essentially aimed at helpinge-mail recipients to filter (select) which automatically e-mail right from spam e-mail, saving time andtenaga.Hasil analysis showed that not only technical factors such as the architecture of e-mail system andauthentication process that factors in SPAM, but also other factors such as less sweeping application ofsecurity policy (security policy), and economic factors such as cost of sending an e-mail is low.Keyword: E-mail, Spam, E-mail filter,SMTPI Methodics